Important factors in municipality-based pediatric palliation from healthcare professionals’ perspective: A qualitative study - Kristin Skjærseth; Natalie Preminger; May Aasebø Hauken (Palliative Care and Social Practice)
Background: Municipality-based pediatric palliative care (PPC) is recommended to promote the quality of life for the child and family by enabling them to stay at home as much as possible. However, municipality-based PPC presents complex challenges and places significant demands on healthcare professionals. Yet, it remains an underexplored field. Objectives: Semi-structured and individual interviews with 16 healthcare professionals with experiences from PPC were conducted and transcribed. Data was analyzed using systematic text condensation. Results: To increase the knowledge base and understanding of important factors for municipality-based PPC from healthcare professionals’ perspective. Design: A qualitative method with an interpretive descriptive design was applied. Methods: The bridging theme “Establishing a sense of security and predictability for the family and healthcare professionals” emerged from the analysis. This was elaborated by three main themes: (1) “A comprehensive approach to the family,” (2) “Establishing and maintaining a dedicated, multidisciplinary pediatric palliative team in the municipality,” and (3) “Collaboration and communication between involved services.” Each main theme was further elaborated by subthemes. Conclusion: The importance of establishing security and predictability in municipality-based PPC was emphasized. To achieve this, holistic support for the entire family and ensuring sufficient competence in the municipality seem crucial. Establishing municipality PPC teams is proposed, and the need for early referral, routines for collaboration, and a designated coordinator appear to be key systemic factors. Registration and reporting guidelines: The study is registered in the institutional system for research project (RETTE ID: R2082), and the study is reported according to the COREQ checklist for qualitative studies.